Another Look at the Silver Jewellery from Psarjevo near Zelina in Northwestern Croatia (Archaeologia Adriatica, 2008)
Silver jewellery from Gornje Psarjevo is observed in the context of new finds and interpretations in Romania as well as in southern Pannonia. The endeavour aims at filling up the picture of events taking place during the 1st cent. B.C., when the jewellery probably arrived in the country.
Keywords: silver jewellery (necklace) from Psarjevo; Dacian silver jewellery; barbarian silver coins; connections with the Dacian production circle